2019
DOI: 10.1152/ajprenal.00178.2018
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of altering oxygenation during kidney normothermic machine perfusion

Abstract: Kidney normothermic machine perfusion (NMP) has historically used a 95% O2-5% CO2 gas mixture. Using a porcine model of organ retrieval, NMP, and reperfusion, we tested the hypothesis that reducing perfusate oxygenation ([Formula: see text]) would be detrimental to renal function and cause injury. In the minimal ischemic injury experiment, kidneys sustained 10 min of warm ischemia and 2 h of static cold storage before 1 h of NMP with either 95%, 25%, or 12% O2 with 5% CO2 and N2 balance. In the clinical injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…However, little is known about whether higher CPB oxygenation is an independent risk factor for AKI following Tetralogy of Fallot repair. A recent experimental report from Adams and colleagues 11 investigated the potential effect of reducing the PpO2 on renal function. In this minimal ischaemic injury experiment, reducing the PpO2 did not significantly influence renal function overall, in terms of no differences developing in the injury markers, urinary neutrophil gelatinase-associated lipocalin or tissue high-motility group box protein 1, which suggested that reducing the PpO2 does not have detrimental effects on renal function or markers of injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about whether higher CPB oxygenation is an independent risk factor for AKI following Tetralogy of Fallot repair. A recent experimental report from Adams and colleagues 11 investigated the potential effect of reducing the PpO2 on renal function. In this minimal ischaemic injury experiment, reducing the PpO2 did not significantly influence renal function overall, in terms of no differences developing in the injury markers, urinary neutrophil gelatinase-associated lipocalin or tissue high-motility group box protein 1, which suggested that reducing the PpO2 does not have detrimental effects on renal function or markers of injury.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, high fractional sodium excretion (FeNa) (usually >1%) is suggestive of tubular necrosis [80]. Several normothermic perfusion models, making use of pig kidneys or kidneys found not suitable for transplantation, report FeNa with a high variability and a wide range (5%-200%) [81][82][83][84][85]. Extrapolating in vivo findings, it seems logical that the lower the FeNa during normothermic perfusion, the better tubular function is preserved.…”
Section: Nephron Functionmentioning
confidence: 99%
“…Therefore, measuring oxygen consumption could be a potential viability marker. Indeed, oxygen consumption is measured in different models as a marker of kidney metabolic activity [81,84,85,88]. What limits direct comparison between studies is the use of a multitude of formulas to calculate oxygen consumption.…”
Section: Nephron Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated the benefits of oxygenating the perfusion solution already during hypothermic perfusion by reducing oxidative stress and supporting the energy status in presence of low metabolic rates (50,51). During sub-normothermic to normothermic perfusion the increased metabolism demands an appropriate oxygen supply, but recent studies indicate that normothermic perfusion with reduced perfusate oxygenation for a limited period of time may also be possible without severely compromising renal function or tissue integrity (52).…”
Section: Immuno-engineering Of the Kidneymentioning
confidence: 99%